The pressure fl ow relationship of the internal mammary artery after offpump anastomosis to the left anterior descending coronary artery - Connellan, Mark B.; Roos, Stephanus J.; Coetzee, André R.; Rossouw, Gawie J. (SA Heart Journal, 2017)
Objective: To assess the pressure flow relationship of the internal mammary artery (IMA) in situ, after skeletonisation and after anastomosis to the left anterior descending (LAD) coronary artery, using either halothane, sevoflurane or propofol as an anaesthetic agent. Methods: 15 Pigs were used in total, five received halothane, five sevoflurane and five propofol as an anaesthetic agent. The flow in the internal mammary artery in each of the pigs, was measured at various arterial pressures. This was done with the IMA in situ, then after dissecting the artery off the chest wall using the skeletonisation technique and finally after offpump grafting to the left anterior descending coronary artery. Results: The pressure flow relationship of the internal mammary artery after skeletonisation was found to be linear (r=0.8650). The pressure flow correlation after grafting the skeletonised internal mammary artery to the left anterior descending coronary artery was found to be similarly linear (r=0.8766). In the sevoflurane subgroup, with the IMA still in situ, a degree of autoregulation was found to be present, but after skeletonisation this was subsequently lost (p=0.011). Conclusions: The pressure flow relationship in the internal mammary artery after skeletonising the vessel and after OPCAB anastomosis to the LAD was found to be linear. In the subgroup of pigs receiving sevoflurane, some degree of autoregulation was demonstrated in the in situ IMA. This remnant of autoregulation was lost after skeletonisation and after grafting of the vessel to the left anterior descending coronary artery. SAHeart 2009; 6:222-228